A journey through poetry of José Antonio Mazzotti: about El Zorro y la Luna. Poemas reunidos 1981-2016 - Santiváñez, Roger (2018)
Criticism and testimony, based on the José Lezama Lima special poetry prize awarded by Casa de las Américas to the book mentioned in January 2018.